Significance of farming groups for resource access and livelihood improvement of rural smallholder women farmers. Issue 5 (3rd July 2020) - Othman, Mwanajuma S.; Oughton, Elizabeth; Garrod, Guy
ABSTRACT: Farming groups are supposed to increase members' access to inputs, equipment and better prices for their crops through collective marketing. Through qualitative methods, the study observed that women farming-group members have improved their access to agricultural resources and shifted to better farming methods. Ultimately, they have improved their productivity, incomes and, livelihoods. However, groups have demonstrated different abilities in terms of meeting member needs, due to differences in the capabilities of individual group members. Extra support and capacity building should be provided to women by supporting organisations to enable them to maximise their achievement in agricultural cooperatives.